A NOTE ON BOOLEAN SUBSETS OF ORTHOMODULAR POSETS - Dorninger, Dietmar; L¨anger, Helmut (Italian Journal of Pure and Applied Mathematics, 2014)
Modelling quantum systems by orthomodular posets \(P\) = (P, ≤, ‘ , 0, 1) gives rise to the question, when a finite subset A of P lies within a Boolean subalgebra of \(P\), in which case A is called Boolean. Boolean subsets A specify the physical subsystem represented by A to be classical. We give a characterization of a subset of P to be Boolean by only taking into account terms of elements of this subset and in such a way that an inductive algorithm can be derived.